Investigating the seasonal predictability of significant wave height in the West Pacific and Indian Oceans. Issue 7 (6th April 2016) - Lopez, Hosmay; Kirtman, Ben P.
Abstract: This study investigates seasonal prediction skill of significant wave height (SWH) in the West Pacific and Indian Oceans. We forced the WAVEWATCH III model with 10 m winds from the National Centers for Environmental Prediction Reanalysis‐2 and from the Community Climate System Model version 4 North American Multi‐Model Ensemble retrospective forecasts for the period of January 1979 to December 2013. Results indicate potential for predicting SWH with several months lead time during boreal summers after the warm phase of El Niño–Southern Oscillation (ENSO) measured by deterministic and probabilistic skill scores in the Northwest Pacific and Bay of Bengal. During these summers, SWH is smaller than normal due to reduced atmospheric synoptic activity associated with an anomalously anticyclone in the western Pacific, leading to larger signal‐to‐noise ratio in the 10 m winds, hence increasing SWH prediction skill. It is shown that ENSO has a nonlinear influence on the number of extremely large SWH events, with reduced number of extreme occurrences during boreal summers after the warm phase of ENSO. Key Points: Seasonal predictability of significant wave height in the Indo‐Pacific Ocean is investigated There is potential for predicting wave height with several months lead time during boreal summers ENSO has a nonlinear influence on the number of extreme significant wave height events